2021
DOI: 10.1021/acs.jpcb.0c10124
|View full text |Cite
|
Sign up to set email alerts
|

SRLS Analysis of 15N–1H NMR Relaxation from the Protein S100A1: Dynamic Structure, Calcium Binding, and Related Changes in Conformational Entropy

Abstract: We report on amide (N−H) NMR relaxation from the protein S100A1 analyzed with the slowly relaxing local structure (SRLS) approach. S100A1 comprises two calcium-binding "EF-hands" (helixloop-helix motifs) connected by a linker. The dynamic structure of this protein, in both calcium-free and calcium-bound form, is described as the restricted local N−H motion coupled to isotropic protein tumbling. The restrictions are given by a rhombic potential, u (∼10 kT), the local motion by a diffusion tensor with rate const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…c 0 2 evaluates the strength of the local potential, and c 2 2 evaluates its rhombicity . In previous work, we found that Z OF is typically pointing along the C α –C α axis. , This ordering characteristic was also determined by other methods. …”
Section: Theoretical Backgroundmentioning
confidence: 61%
See 3 more Smart Citations
“…c 0 2 evaluates the strength of the local potential, and c 2 2 evaluates its rhombicity . In previous work, we found that Z OF is typically pointing along the C α –C α axis. , This ordering characteristic was also determined by other methods. …”
Section: Theoretical Backgroundmentioning
confidence: 61%
“…Thus, R ex is likely to act as a fit parameter. As shown in a recent study, in such cases the results can be substantially impaired. This might be the reason for only S 2 being reported out of the four parameters comprising the five MF models.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Related approaches employ discrete or continuous distributions to more fully capture the range of intramolecular correlation times (Lemaster, 1995;Calandrini et al, 2010;Khan et al, 2015;Hsu et al, 2018Hsu et al, , 2020Smith et al, 2019). Other strategies employ physical models or atomistic molecular dynamics simulations for overall rotational diffusion and internal conformational fluctuations, to more directly link the NMR phenomena to underlying physical processes (Tugarinov et al, 2001;Zerbetto et al, 2013;Ollila et al, 2018;Polimeno et al, 2019a, b;Mendelman et al, 2020;Mendelman and Meirovitch, 2021). The availability of extended model-free formalisms, or other approaches with variable numbers of parameters, has created a further dilemma: should a data analysis protocol extract the most exacting information justified by the data or employ the model most robust to experimental variation?…”
Section: Introductionmentioning
confidence: 99%